The influence of thermal treatment on the preparation of PNM and PMN-PT thin films - Spagnol, P. D.; Valadares, L. F.; Varela, José Arana [UNESP]; Bertochi, MAZ (Elsevier B.V., 2003)
Ferroelectric thin films belong to a class of materials with great technological importance in optic fibers, micro-electromechanical systems, and microprocessors and computers memories.The (1-x)PbMg1/3Nb2/3O3(x)PbTiO3 (PMN-PT) thin films, with x=0, 0.1, 0.35 and 0.5, were prepared by Pechini's process and deposited by spin-coating on Si(100), Pt/Ti/SiO2/Si(100) and quartz substrates. The goal of the present paper is to verify the thermal treatment influence on the perovskite phase formation, which is desirable for these applications. The phase formation was analyzed by X-ray diffraction. The film's surface was characterized by atomic force microscopy to analyze the roughness and the homogeneity. The results of this study indicate that the optimum conditions for obtaining the perovskite phase using a Pt/Ti/SiO2/Si(100) substrate, were drying each deposited layer at 140 degreesC (heating plate), and a final thermal treatment at 600 degreesC for 3 h in a closed system with a lead-rich atmosphere. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: thermal treatment; ferroelectric thin films; PMN thin films; PMN-PT thin films